Structural studies on some enterobacterial capsular antigens - Whittaker, Darryl Vanstone (Rhodes University, Faculty of Pharmacy, Pharmacy, 1994)
The investigations presented in this thesis form part of a systematic international effort to establish the structures of the capsules produced by the bacterial genera, Escherichia coli and Klebsiella (family enterobacteriaceae). These bacteria are of medical interest as they are opportunistic pathogens and are frequently responsible for serious infections in animals and man. Invasive strains are invariably surrounded by a structurally complex polysaccharide capsule which contributes to the organism's ability to attenuate non-specific host defence mechanisms or, in some instances, to completely prevent an immune response. A knowledge of the chemical composition and structure of the capsule is, therefore, of great value as it provides insight into the mechanisms involved in this process. The E. coli, in particular, have generated considerable interest as their capsules are more structurally diverse and cross-reactivity with other, more pathogenic bacteria has also been demonstrated. Accordingly, the structures of three previously unstudied E. coli K-antigens viz. those produced by serotypes 020:K83:H26, 020:K84:H26, and 09:K48:H9 have been established by chemical and spectroscopic means and are presented in this thesis. In addition, a reinvestigation of the structure of the capsule produced by Klebsiella K15 using a novel enzymatic approach was also undertaken and a revised structure is proposed . The E. coli K48 polysaccharide is of special interest as it was found to contain a new diacetamido trideoxy hexose hitherto unrecorded. A synthesis for this saccharide is also presented. Finally, the application of lithium dissolved in ethylenediamine for the degradation of amino sugar-containing polysaccharides was also investigated using the capsular polysaccharides produced by E. coli serotypes K38 and K84 as model compounds.
Keywords: Bacterial antigens -- Analysis; Antigens; Enterobacteriaceae; Escherichia coli; Klebsiella